ANALISIS TERJEMAHAN TEKS AKADEMIK MAHASISWA PROGRAM STUDI PENDIDIKAN BAHASA ARAB - N. Lalah Alawiyah; Ahmad Royani; Mukhshon Nawawi (Arabiyat : Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2016)
This research was aimed to deal with the research question about how the strategy was used to translate Indonesian language academic texts into Arabic in structural aspect, its strategy in semantical aspect, and its appropriateness in terminological aspect. Qualitative research was applied in this study and content analysis was used for the analysis. The source of this research was the authentic examples of the students’ work Department of Arabic Language FITK UIN Syarif Hidayatullah in translation subject. The data used in this study were the verbal expressions in students’ works. The result found from 150 identified strategies, it was found 7 translation strategies discovered from students’ works from Indonesian language into Arabic. Based on the strategies found, it can be concluded that the translation of academic texts was still oriented to the first language. From the aspect of target language, the academic terminology was appropriately used, standardized and clear, although some mistakes found from the aspect of structure.DOI: 10.15408/a.v3i2.4642